2005
DOI: 10.1557/jmr.2005.0418
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of indentation-induced densification in glass

Abstract: To estimate the ratio of densification to Vickers indentation volume, three-dimensional images of Vickers indentations on several glasses, including silicate glasses and bulk metallic glass (BMG), were obtained before and after annealing using an atomic force microscope. Large volume recovery of Vickers indentation by annealing was observed for all glasses but BMG. Following previous studies, this recovered volume almost corresponded to the densified volume under a Vickers indenter, and the compositional depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
282
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(302 citation statements)
references
References 25 publications
17
282
3
Order By: Relevance
“…In general, both processes, densification and shear flow are sensitive toward changes in strain rate (Shikimaka et al, 2016); the contribution of each, however, depends on composition, atomic packing density, and network connectivity (Yoshida et al, 2005;Limbach et al, 2014;Möncke et al, 2016). Shikimaka et al (2016) concluded densification to be triggered by shear and pressure.…”
Section: The Effect Of Strain Rate On the Deformation Mechanismmentioning
confidence: 99%
“…In general, both processes, densification and shear flow are sensitive toward changes in strain rate (Shikimaka et al, 2016); the contribution of each, however, depends on composition, atomic packing density, and network connectivity (Yoshida et al, 2005;Limbach et al, 2014;Möncke et al, 2016). Shikimaka et al (2016) concluded densification to be triggered by shear and pressure.…”
Section: The Effect Of Strain Rate On the Deformation Mechanismmentioning
confidence: 99%
“…This indenter undergoes a moderate displacement in the z direction until the reacting force reaches the desired indentation force. Table 4 presents a comparison between the experimental [8,32] and the present numerical indentation results for low indentation forces (F indent = 0.1 N and F indent = 0.5 N). For F indent = 0.1 N, the DEM simulation yielded a relatively good estimate of the volume of the indentation print V − and the volume of the piled-up material around the indenter V + .…”
Section: Vickers Indentationmentioning
confidence: 99%
“…In that respect glasses do not differ from standard materials, except that the characteristic length scale below which volume deformation (plasticity) is energetically more favorable than surface creation (crack propagation) is smaller [3]. Although known for half a century [4] and of primary interest for many micron-scale applications, the plasticity of silicate glasses has up to now remained little studied [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%